Representation of tri hita karana in megoak-goakan game and its implementation in physical education - Dartini, Ni Putu Dwi Sucita; Sutajaya, I Made; Suja, I Wayan; Astawa, Ida Bagus Made (Jurnal Ilmu Keolahragaan, 2024)
Traditional games are activities that grow and develop in an area that is played from generation to generation are rich in cultural values that can be a means in the physical education learning process. This research aims to examine the values of Tri Hita Karana in megoak-goakan game and examine its implementation in physical education. The method used in this research is literature study by reviewing books, articles, journals, notes and reports related to the topic. The results showed that the megoak-goakan game represented the values of Tri Hita Karana, namely (1) harmonization with God (Parahyangan) in the form of religious rituals before starting the game, (2) harmonization with humans (Pawongan) in the form of cooperation, responsibility and mutual respect, and (3) harmonization with nature (Palemahan) in the form of maintaining cleanliness and preservation of the yard where to play. The megoak-goakan game can be implemented in physical education learning because it is proven to improve motor skills, physical fitness, develop social and emotional skills and pass on cultural values that are full of national character values.